Optimal Design of Multi-Purpose Sandwich Beam-Columns - R.D. Parbery; B.L. Karihaloo (Engineering Transactions, 1979)
The paper deals with the minimum-weight design of pin-ended members that have to act as a beam in some situations and as a column in others. The space of design constraints is divided into regions in which the optimal design is governed by either one of the two design requirements or both. The method is illustrated by the example of a member having a linear relationship between stiffness and cross-sectional area (mass). The economy achieved by optimization is discussed.